BANKRUPTCY OF THE COMPANY AS A CONSEQUENCE OF MANIPULATIVE FINANCIAL REPORTING - Bešlić, Dragana; Bešlić, Ivana (International Journal of Economic Practice and Policy, 2014)
Business of companies in terms of  financial instability and market uncertainty can lead to a significant increase in bankruptcy risk and the risk of financial statements manipulation. A creative accounting  practice has led many companies in the world to bankruptcy. Creative accounting means all accounting practices that deliberately deviate from the standardized ones, in order for the external users to be presented with the desired, not the actual yield and the financial strength of the company. Numerous corporate accounting scandals were the cause for initiatives to strengthen the protection of shareholders and all other interested users of financial statements (investors, creditors, tax authorities, etc.) from manipulative financial reporting in countries around the world. In such circumstances, responsibility for the detection and prevention of possible manipulation with the data presented in the financial statements have: external and forensic audit, internal control and management of the company, accountants - forensics and state.
Keywords: BANKRUPTCY; creative accounting; financial reporting; accounting scandals; misuse of bankruptcy; preventing manipulation; COMPANY